The New Science - Vico, Giambattista (Yale University Press, 2020)
A fresh translation of The New Science, with detailed footnotes that will help both the scholar and the new reader navigate Vico's masterpiece The New Science is the major work of Italian philosopher Giambattista Vico. First published in 1725 and revised in 1730 and 1744, it calls for a reinterpretation of human civilization by tracing the stages of historical development shared by all societies. Almost unknown during his lifetime, the work had a profound influence on later thinkers, from Montesquieu and Marx to Joyce and Gadamer. This edition offers a fresh translation and detailed annotations which enable the reader to track Vico's multiple allusions to other texts. The introduction situates the work firmly within a contemporary context and newly establishes Vico as a thinker of modernity.